Association of Tumor Necrosis Factor-Alpha (TNF-α) and Suppressor of Cytokine Signaling-1 (SOCS-1) Gene Variants in Children with COVID-19 - Uysalol, Metin; Serin, Istemi; Oyacı, Yasemin; Yıldız, Raif; Uysalol, Ezgi; Pehlivan, Sacide (Journal of Pediatric Infectious Diseases, 2022)
Objective The suppressor of cytokine signaling-1 (SOCS-1) gene is an essential physiological regulator of cytokine signaling. Tumor necrosis factor-α (TNF-α) is an important component of the immunological response. Herein, we aimed to investigate the effects of SOCS-1 (-1478 CA > Del) and TNF-α (-308) polymorphisms on disease susceptibility and prognosis in pediatric patients with coronavirus disease 2019 (COVID-19).Methods One-hundred fifty COVID-19 patients in the COVID-19 emergency department between September 2020 and April 2021 and 80 healthy volunteers (control group) without any additional disease were included. Baseline gene polymorphisms were compared between the patient and healthy control groups. Afterward, the gene polymorphism distribution was examined by forming two separate clinical patients' subgroups.Results While CA/CA and CA/Del gene variants of SOCS-1 were higher in the patient group, Del/Del genotype was more common in the control group (p < 0.05). The GG genotype of the TNF-α was significantly more common in the severe subgroup (p = 0.044). The GA genotype of TNF-α was associated with the risk of hospitalization (2.83-fold), while the GG genotype was found to be protective in terms of hospitalization (2.95-fold).Conclusions This study will be a guide in terms of the presence of high cytokine release genotypes and COVID-19-related cytokine release syndromes.
Keywords: COVID-19; SOCS-1; TNF-α; cytokines